Comparative ecology of sympatric storm-petrels: Breeding biology, niche segregation, and response to environmental changes - Bedolla Guzmán, Yuliana Rocío; Justus Liebig University Giessen (My University, 2025)
Seabirds, including storm-petrels, are integral to marine ecosystems, yet significant gaps persist in understanding their ecology. This PhD thesis examines the niche segregation, breeding biology, and responses to environmental variability of three sympatric storm-petrel species: Leach’s storm-petrel (Hydrobates leucorhous), which is widely distributed across the Atlantic and Pacific Oceans, and the black storm-petrel (Hydrobates melania) and least storm-petrel (Hydrobates microsoma), both restricted to the Eastern Tropical Pacific. These species breed in sympatry on the San Benito Archipelago, Mexico, which supports a population of approximately two million individuals. The thesis aims to advance knowledge of their resource use, reproductive strategies, and adaptive responses to environmental changes, addressing critical gaps in their ecological understanding. The research is structured into three chapters, each exploring distinct ecological aspects. Chapter 1 evaluates niche segregation among the three storm-petrel species using stable isotope analysis of carbon (δ13C) and nitrogen (δ15N) from tissues such as blood, feathers, and egg membranes, along with diet samples collected in 2012–2013. A marine isoscape was constructed using krill samples from the Pacific waters off Baja California. The findings demonstrated significant dietary and isotopic niche segregation during the breeding season, with black storm-petrels consuming high-trophic-level krill from neritic waters, while Leach’s and least storm-petrels fed on lower-trophic fish larvae in oceanic regions. Additionally, black storm-petrels exhibited shifts in foraging strategies across breeding phases, reflecting dietary flexibility. Chapter 2 focuses on the breeding biology of the least storm-petrel, investigating breeding phenology, reproductive success, chick growth, and diet over three breeding seasons (2013–2015). Eggs, chicks, and adults were monitored, and diet samples were collected to evaluate feeding ecology. Morphometric differences between sexes were analyzed using mist-net captures and molecular sexing in 2012. Results revealed consistently high breeding success, with inter-annual variations in timing of breeding and chick growth linked to anomalous climate conditions. Females exhibited longer wings and tails than males, while dietary analyses identified larval fish, euphausiids, and squid as key prey items. Chapter 3 investigates inter-annual variability in the breeding biology, chick growth, and provisioning behavior of the black storm-petrel over six consecutive breeding seasons (2012–2017). Parameters such as peak mass, fledging mass, feeding rate, and meal size showed significant inter-annual variation, although these trends were not explained by regional or local environmental indices. This suggests that other factors such fine-scale habitat or pre-breeding ocean conditions may play a more influential role in shaping these reproductive traits. In conclusion, this thesis provides valuable insights into the resource partitioning, breeding biology, and adaptive strategies of storm-petrels, highlighting the importance of niche segregation in facilitating coexistence and reducing interspecific competition. The results emphasize the need to account for environmental variability and anthropogenic pressures in conservation strategies. By contributing to a broader understanding of storm-petrel ecology, this work establishes a foundation for enhancing conservation and management efforts for these and other seabird species in dynamic and rapidly changing marine ecosystems.
Keywords: Seabirds; Storm-petrels; Niche segregation; Breeding biology; Environmental variability; ddc:570; ddc:590